Informal social control and community crime prevention - Foster, Janet (The British journal of criminology, 1995)
The absence of informal social control is frequently thought to play a major role in levels of crime. Tet relatively little research has focused directly on the role of informal social control in high crime areas. This article based on ethnographic research describes a London housing estate that had statistically higher than average rates of crime and many of the design failures' of public housing. Tet crime was not perceived to be a problem' by the residents who lived there. The description suggests that particular features of the estate including its resident and demographic profile, geographic location, and the presence of some degree of informal social control enabled tenants to contain crime. The article concludes that the role of informal social control in high crime areas and the relationship between crime and public housing is more problematic than many commentators have suggested